Socio-Cultural Factors Influencing Medical Circumcision of Males Performed Voluntarily Uptake in Turkana County - Lokorio, Ekidor Ateyo; Mwanzo, Isaac; Ogweno, Gordon (European Journal of Health Sciences, 2024)
Purpose: Kenya is amongst six high-burden nations in Africa grappling high HIV infections. Approximately 91.2% of Kenyan men have undergone circumcision. However, male circumcision is not traditionally practiced in Turkana community with male circumcision rates ranging from 5-10%. The study's sought to identify socio-cultural factors Influencing Medical Circumcision of Males Performed Voluntarily Uptake in Turkana County. Materials and Methods: Utilizing a researcher-administered survey, KII schedules, and a FGD guide, data was gathered. 434 males made up the sample size. An analytical cross-sectional methodology was used in the investigation. The data was analyzed with SPSS 22. Results showed that of 374 male participants in the study, 79.9% had undergone circumcision, 77.0% were aged 18-35 years, 94.1% were Christians, and 44.7% were unemployed while 54.8% were married. The overall mean scores of responses for socio-cultural factors, psychosocial factors, socio-economic factors, and information sources factors were 3.230 (neutral), 3.602 (positive), 2.894 (negative) and 3.48 (neutral), respectively. Findings: The study found that socio-cultural factors was significant predictors of embracing VMMC. Sociocultural factors were about 0.30 times more likely to increase uptake of VMMC [OR=0.301; 95% CI: 0.081-0.52, P=0.007]. Conclusion: The study recommends that policies addressing main VMMC uptake amongst men in Turkana County should incorporate public participation, traditional leaders and local administrators for societal acceptance. There is need for effective sensitization and advocacy for behavioral change, mobilization and ownership of the initiative by the community. Policies should advocate for local leadership training.